Factors shaping cartographic representations of inequalities. Maps as products and processes. (February 2016) - Martínez, Javier; Pfeffer, Karin; Baud, Isa
Abstract: This paper analyses factors shaping cartographic representation of inequalities and discusses new forms of deprivation mapping. A heuristic framework with three dimensions shaping representations of inequalities is built, using examples from cities in the global South and North. Dimensions include the framing of inequalities, sources from which knowledge is produced, and geographic scales to which information and analysis refers. This framework is combined with a discussion on the genealogy of map production and use, in order to assess the extent to which maps can be catalysts for equitable social change. Results show that an approach recognizing the multi-dimensionality of spatial inequalities, combining different knowledge sources and including critical awareness of existing geographic boundaries at different scales and their limitations, is necessary to interpret maps well. We suggest that a hybrid approach integrating the three dimensions which reflect how major choices are made, provide a more holistic understanding of how urban poverty maps are produced. The potential transformative power of maps lies in being catalysts for discussions and stimulating debates. Highlights: We analyse factors shaping inequalities and deprivation mapping. We develop a heuristic framework and discuss genealogy of map production. We utilize examples from cities in the global South and North. Need to recognize multidimensionality of inequalities and knowledge sources. Critical awareness of existing boundaries at different scales and transformative power of maps.